Expatriate Management and Spouses : Challenges and Service Opportunities in Helsinki Region - Najafi, Ali (My University, 2023)
The aim this thesis is to identify the challenges faced by expatriates’ spouses in the Helsinki capital region and how multi-nation companies (MNCs) and public sector can further assist the expatri-ates’ spouse overcoming these challenges. The study also explores potential areas for improve-ment in supporting expatriates and their spouses through analysis global mobility of 3 different MNCs located in Helsinki capital region, the current service offering from public sector and munici-palities, and the services provided by third-party relocation service providers. The research methodology used in this thesis involves a literature review and empirical data col-lection. The literature review of the thesis focuses on existing literature on expatriate manage-ment, including literature on family adjustment models and theories, impact of family members on expatriate’s performance, family members as a stakeholder for MNCs, as well as the current or-ganizational practices for supporting the expatriates’ spouses. Empirical data was collected through interviews with ten expatriate spouses living in Helsinki (who have relocated to Helsinki capital region due to their spouse’s assignment and whom don’t have a Finnish national spouse), as well as an analysis of global mobility policies of three different MNCs in the region, third-party relocation service providers, and services offered by city officials and public sector. The findings suggest that expatriate spouses face several challenges when relocating to Helsinki, including feeling neglected, language barriers, difficulties related to finding a suitable career oppor-tunity, and cultural differences and adjustment. Multi-national companies in the region have im-plemented various practices to support expatriates and their families. In addition, the MNCS have hired services from their-party relocation service provider to further assist the spouses. Further-more, governmental parties provide the expatriates’ spouse with integration programs, language courses, and social networking opportunity. However, there is still room for improvement in terms of providing more comprehensive support services that address the specific needs of expatriates’ spouses. The study recommends early consideration of family needs by MNCs from the beginning of talent attraction process. The study suggests increase of involvement of spouses in the recruitment pro-cess, relocation, and immigration process, and increase of interactive communication by MNCs, public sector and relocation service providers towards the expatriates’ spouses. Finally, this thesis highlights the importance of providing comprehensive support for expatriates’ spouses and early communication related to the current services and future possibilities before the relocation process has started.
Keywords: expatriates; working abroad; spouses; mobility; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development